Analysis of Dump Truck Spare Parts Inventory Control Using the EOQ Lot Sizing Method at PT XYZ - Alnadhif, Delvio Raditya; Sitania, Farida Djumiati; Wahyuda (Journal Knowledge Industrial Engineering (JKIE), 2025)
PT XYZ operates in hauling, mining, and road maintenance. At one of its operational sites, the company only orders spare parts when stock runs out, leading to frequent orders, increased operational costs, and disruptions due to stock shortages. Effective inventory management is essential to ensuring sufficient stock availability while minimizing costs. This study focuses on optimizing spare parts inventory for Dongfeng dump trucks using the Economic Order Quantity (EOQ) method. EOQ determines the optimal order quantity by balancing ordering and holding costs, aiming to reduce total inventory expenses. Demand forecasting is conducted to support inventory optimization. The findings indicate that implementing EOQ significantly lowers total inventory costs compared to the company’s current approach. The EOQ model results in a total inventory cost reduction of 39.15%, saving IDR 10,514,286. The analysis highlights that ordering and holding costs play a crucial role in inventory expenses. These insights can serve as a reference for PT XYZ in developing more efficient inventory management policies to improve operational continuity and reduce the risk of downtime due to spare parts shortages.